SMART LOGIN PADA WEBSITE DENGAN MENGGUNAKAN QR CODE DAN OTENTIKASI ONE TIME PASSWORD - Lois Adelson; Dodi Siregar; Kalvin Chiuloto (Universitas Harapan Medan, 2020)
The use of passwords has been used in many ways such as logging into a website application. However, most of these passwords still use static passwords, making them vulnerable to tapping login passwords. There are many ways that hackers can do to hack into websites that use a login system, such as phishing techniques. Layered security is required to secure the login system, the use of the OTP code is one way of verification and can only be accessed by the user himself so that it can reduce the potential for wiretapping of access rights. The application of QR Code technology is quite practical and provides an easy solution to enter the system. Users don't need to log in by entering their username and password repeatedly, just pointing the QR Code at the webcam to be scanned. To increase login security to prevent intrusion into the system, authentication is made in the form of a unique, single-use code called One Time Password (OTP). The password that previously used one username and one password will be added to another random password which will be sent to the user's cellular phone via SMS message. This research is able to provide convenience when accessing a QR Code login and increasing security in the system because the OTP code that is sent is only valid for one login session and is valid for only 5 minutes, so the OTP code cannot be reused in the next login session.